THE TEACHING OF VOCABULARY - Musurmonova, Durdona (Журнал иностранных языков и лингвистики, 2021)
Abstract: The learning of vocabulary is an important part in foreign language learning. The meanings of new words are very frequently emphasized, whether in books or in verbal communication. Vocabulary is a basic of one learns a foreign language. Through this article, the writer summarizes the related research that focus on the importance of vocabulary and explains many techniques used by some English teachers and lecturers when teaching English, as well as writer’s personal view of the issues. Keywords: perspective, teaching of vocabulary, vocabulary.